2017
DOI: 10.1515/mper-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organisational Culture on Total Quality Management Implementation and Firm Performance: Evidence from the Vietnamese Construction Industry

Abstract: The main purpose of this study is to examine the relationship between organisational culture (OC) and Total Quality Management (TQM), and the influence of TQM implementation on organisational performance improvement within the context of the Vietnamese construction industry. A survey was conducted with 104 respondents from Vietnamese construction firms, using validated survey instruments developed in past research. Analysis techniques include cluster analysis and Structural Equation Modelling. Findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
(86 reference statements)
4
36
0
5
Order By: Relevance
“…Several authors have highlighted about the scarcity of quality management research over the practices, values, beliefs and assumptions that leverage (or constrain) the behaviors required for their successful implementation and development (Panuwatwanich 2017;Prajogo and McDermott 2005;Detert et al 2003;Detert et al 2000;Zeitz et al 1997). The literature review also confirmed the lack of research in healthcare around interactions between quality and culture, in particular regarding the dimensions or organizational culture and the different patterns of usage of quality management practices (Davies et al 2000;Huq and Martin 2000;Patyal and Koilakuntla 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Several authors have highlighted about the scarcity of quality management research over the practices, values, beliefs and assumptions that leverage (or constrain) the behaviors required for their successful implementation and development (Panuwatwanich 2017;Prajogo and McDermott 2005;Detert et al 2003;Detert et al 2000;Zeitz et al 1997). The literature review also confirmed the lack of research in healthcare around interactions between quality and culture, in particular regarding the dimensions or organizational culture and the different patterns of usage of quality management practices (Davies et al 2000;Huq and Martin 2000;Patyal and Koilakuntla 2018).…”
Section: Introductionmentioning
confidence: 94%
“…QA in SME construction projects is one part of quality system management. QA involves establishing project-related policies, procedures, standards, training, guidelines and systemic activities implemented in a quality system to fill quality requirements (Basu, 2004;Freeman-Bell & Balkwill, 1996;Aziz & Abdel-Hakam, 2016;Panuwatwanich & Nguyen, 2017). Having specific procedures, clear policies, standards, training, guidelines and systems designed to maximize employee performance in facilitating a business' strategic objectives correlates with project success by directing attention, motivating and maintaining an efficient quality-management system (Arditi & Gunaydin, 1997;Nyakala, 2017).…”
Section: Quality Assurance In Smesmentioning
confidence: 99%
“…SME road contractors must use formal techniques of project management to enable citizens to have quality road networks and access to public services such as education, health facilities, and the movement of labour between workplaces (Vermeulen et al, 2018: 2). In addition, quality controls are required to prevent the deterioration of maintenance backlogs, and focus the efforts of the project manager on the daily control of the numerous activities of the project (Thorpe, Summer & Duncan, 1996;Panuwatwanich & Nguyen, 2017).…”
Section: Project Planning and Control Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 shows the steps of SEM. Those steps are (1) model specification, (2) data collection, (3) model identification, and (4) model testing (Panuwatwanich & Nguyen, 2017).…”
Section: Structural Equation Modelingmentioning
confidence: 99%